Modulation of metabolic alterations of obese diabetic rats upon treatment with Salacca zalacca fruits extract using H NMR-based metabolomics - Saleh, Mohammed S M; Siddiqui, Mohammad Jamshed Ahmad; Mediani, Ahmed; Ahmed, Qamar Uddin; Mat So'ad, Siti Zaiton; Saidi-Besbes, Salima; Elnaem, Mohamed Hassan Abdelaziz; Othman, Hairol Azrin; Ismail, Nor Hadiani (Elseviers, 2020)
Fruit of salak (Salacca zalacca) is tradition ally used and commercialized as an an tidiabetic agent. How ever, the scientific evidence to prove this traditional use is lack ing. This re search was aimed to evaluate the metabolic changes of obese-diabetic (OBDC) rats treated with S. zalacca fruit using proton-nuclear magnetic resonance ( H NMR)-based metabolomics approach. This re search presents the first report on the in vitro antidiabetic effect of S. zalacca fruits ex tract us ing this approach. The obtained results in dicated that the administration of 400 mg/ kg bw of 60% ethanolic S. zalacca extract for 6 weeks significantly de creased the blood glucose level and normalized the blood lipid pro file of the OBDC rats. The potential biomarkers in urine were 2-oxoglutarate, alanine, leucine, succinate 3-hydroxy butyrate, taurine, betaine, allantoin, acetate, dimethylamine, creatine, creatinine, glucose, phenyl-acetyl glycine, and hippurate. Based on the data obtained, the metabolite pro files of the urine of treated rats by the 60% ethanolic extract could not be fully improved the metabolic complications of diabetic rats. The ex tract of S. zalacca fruit was able to de crease the ketones bodies as 3-hydroxy butyrate and acetoacetate. It has also improved energy metabolism, involving glucose, acetate, lactate, 2-hydroxy butyrate, 2-oxoglutarate, citrate, and succinate. More over, it decreased metabolites from gut microflora, including choline. This extract had significant effect on amino acid metabolism, metabolites from gut microflora, bile acid metabolism and creatine. The result can further support the traditional claims of S. zalacca fruits in management of diabetes. This finding might bevaluable in understanding the molecular mechanism and pharmacological properties of this medicinal plant for managing diabetes mellitus.